¿Se puede predecir el grado histopatológico de un meningioma? - Vilariño, Augusto (Revista Argentina de Neurocirugía, 2022)
Abstract Background: Meningiomas are common intracranial tumors. They are generally characterized as benign slow-growing lesions. Surgical resection is the treatment of choice. However, certain meningiomas can present an aggressive growth pattern with a tendency to recurrence and, in rare cases, distant metastases. Magnetic Resonance Imaging (MR) and Computed Tomography (CT) images have been studied in order to identify signs and characteristics which could be related to higher-grade meningiomas. Objective: The objective of this manuscript was to identify features in preoperative images in conjunction with other variables to predict an aggressive biological behavior in meningiomas. Material and methods: An observational retrospective study was conducted evaluating all patients over 18 years of age who underwent surgical resection with a diagnosis of meningioma during the period from January 2015 to December 2019. Epidemiological variables, pathological anatomy and imaging studies were analyzed. Results: During the period studied, 56 patients were diagnosed with meningioma, in which study 39 (70%) were considered low grade and 17 (30%) high grade In the latter group 9 (16%) were grade II and 8 (14%) grade III. Variables such as male sex (p = 0.01), heterogeneous enhancement and low apparent diffusion coefficient (ADC) were statistically significant to predict the malignancy of the lesion. Conclusion: In our study, a positive correlation was observed between male sex, heterogeneous enhancement and low ADC value with aggressive meningiomas.